2013
DOI: 10.1016/j.nicl.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the test–retest reliability of cerebral blood flow measurements in a clinical model of on-going post-surgical pain: A study using pseudo-continuous arterial spin labelling

Abstract: Arterial spin labelling (ASL) is increasingly being applied to study the cerebral response to pain in both experimental human models and patients with persistent pain. Despite its advantages, scanning time and reliability remain important issues in the clinical applicability of ASL. Here we present the test–retest analysis of concurrent pseudo-continuous ASL (pCASL) and visual analogue scale (VAS), in a clinical model of on-going pain following third molar extraction (TME). Using ICC performance measures, we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 54 publications
8
30
0
Order By: Relevance
“…In alignment to several previous test-retest reliability studies of average CBF (Hodkinson et al, 2013;Jahng et al, 2005; Jann et al, 2014), we showed excellent reliability of CBF-mean almost across the whole brain in both EO and EC states. Consistent with previous reliability investigations of BOLD-ALFF in EO (Kublbock et al, 2014;Zuo et al, 2010a), we observed high reliability in the gray matter and most white matter regions and extended the findings to both EO and EC resting states.…”
Section: Test-retest Reliability Of Bold and Cbfsupporting
confidence: 91%
See 4 more Smart Citations
“…In alignment to several previous test-retest reliability studies of average CBF (Hodkinson et al, 2013;Jahng et al, 2005; Jann et al, 2014), we showed excellent reliability of CBF-mean almost across the whole brain in both EO and EC states. Consistent with previous reliability investigations of BOLD-ALFF in EO (Kublbock et al, 2014;Zuo et al, 2010a), we observed high reliability in the gray matter and most white matter regions and extended the findings to both EO and EC resting states.…”
Section: Test-retest Reliability Of Bold and Cbfsupporting
confidence: 91%
“…Test-retest reliability of CBF-mean, BOLD-and CBF-ALFF, and BOLD-and CBF-FC For CBF-mean, consistent with previous voxel-wise test-retest studies (Hodkinson et al, 2013;Jahng et al, 2005;Jann et al, 2014), we showed that both short-and long-term ICC were excellent (ICC N 0.6) for almost the entire brain volume, especially in the gray matter in both EO and EC states (Figs. 2, 3 and S1).…”
Section: Group Average Maps Of Cbf-mean Bold-and Cbf-alff and Bold-supporting
confidence: 90%
See 3 more Smart Citations